2021
DOI: 10.1371/journal.pgen.1009773
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional progression during meiotic prophase I reveals sex-specific features and X chromosome dynamics in human fetal female germline

Abstract: During gametogenesis in mammals, meiosis ensures the production of haploid gametes. The timing and length of meiosis to produce female and male gametes differ considerably. In contrast to males, meiotic prophase I in females initiates during development. Hence, the knowledge regarding progression through meiotic prophase I is mainly focused on human male spermatogenesis and female oocyte maturation during adulthood. Therefore, it remains unclear how the different stages of meiotic prophase I between human ooge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 96 publications
0
13
0
Order By: Relevance
“…In mice, single cell transcriptomics has been applied to investigate the developmental stages and cellular trajectories during male gametogenesis (Chen et al, 2018), but the molecular identity of the rete testis was not explored. Similarly, single cell transcriptomics in humans has been used to study testis development and gametogenesis during fetal and adult life (Fan et al, 2021, Guo et al, 2018, Guo et al, 2021, Li et al, 2017, Shami et al, 2020, Sohni et al, 2019, Wang et al, 2018). However, the molecular signatures of the rete testis have not been inferred and differences with the mesonephros remain to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…In mice, single cell transcriptomics has been applied to investigate the developmental stages and cellular trajectories during male gametogenesis (Chen et al, 2018), but the molecular identity of the rete testis was not explored. Similarly, single cell transcriptomics in humans has been used to study testis development and gametogenesis during fetal and adult life (Fan et al, 2021, Guo et al, 2018, Guo et al, 2021, Li et al, 2017, Shami et al, 2020, Sohni et al, 2019, Wang et al, 2018). However, the molecular signatures of the rete testis have not been inferred and differences with the mesonephros remain to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it's well known that ovary is the female counterpart of the testis, thus scientists tried to compare gonads of two genders. The conservatism of germ cells for both genders was observed during meiotic prophase I, such as the high expression of the same marker genes at each stage of primary SPC/oocytes ( TEX19 in leptotene; SPO11 in zygotene; BRDT in pachytene and H1FOO in diplotene) 172 . Wang et al even identified shared subtypes of germ cells (SPARC + fetal germ cells) in prenatal testes and ovaries 82 .…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al even identified shared subtypes of germ cells (SPARC + fetal germ cells) in prenatal testes and ovaries 82 . But huge heterogeneity of germ cells was also reported in the expression of X-linked genes, including the high expression of SMS in diplotene oocytes but not SPC and the lack of XIST in adult testes 73 , 172 . Both homogeneity and diversity between genders were also reported in somatic cells during scRNA-seq analyses.…”
Section: Resultsmentioning
confidence: 99%
“…In the category of the preinitiation complex (PIC) of transcription, six complexes were detected, and the complex abundance was basically presented in two phase-dependent modes, upregulated in L and Z or P and D. Although the phase-dependent transcription changes in MPI have been studied, the relevant transcription complexes at each phase of MPI have not yet been reported. This study monitored the complex abundance responses to the MPI process for the first time.…”
Section: Resultsmentioning
confidence: 99%